Impact of Grain Sorghum Polyphenols on Microbiota of Normal Weight and Overweight/Obese Subjects during In Vitro Fecal Fermentation - Ashley, Danielle; Marasini, Daya; Brownmiller, Cindi; Lee, Jung Ae; Carbonero, Franck; Lee, Sun-Ok (Nutrients, 2019)
The human gut microbiota is considered as a crucial mediator between diet and gut homeostasis and body weight. The unique polyphenolic profile of sorghum bran may promote gastrointestinal health by modulating the microbiota. This study evaluated gut microbiota and modulation of short-chain fatty acids (SCFA) by sorghum bran polyphenols in in vitro batch fermentation derived from normal weight (NW, n = 11) and overweight/obese (OO, n = 11) subjects’ fecal samples. Six separate treatments were applied on each batch fermentation: negative control (NC), fructooligosaccharides (FOS), black sorghum bran extract (BSE), sumac sorghum bran extract (SSE), FOS + BSE, or FOS + SSE; and samples were collected before and after 24 h. No significant differences in total and individual SCFA production were observed between NW and OO subjects. Differential responses to treatment according to weight class were observed in both phyla and genera. Sorghum bran polyphenols worked with FOS to enhance Bifidobacterium and Lactobacillus, and independently stimulated Roseburia and Prevotella (p < 0.05). Our results indicate that sorghum bran polyphenols have differential effects on gut health and may positively impact gut ecology, with responses varying depending on weight class.